Pengaruh Karakteristik Individual yang Mempengaruhi Gejala Dispepsia Akibat Stress Akademik pada Mahasiswa Selama Masa Pandemi COVID-19 - Indro Harianto; Jane Netta Meilia (STIKes Surya Global Yogyakarta, 2022)
ABSTRACT Background of Study: Functional dyspepsia is a symptom of discomfort in the upper abdomen, feeling full quickly, burning and bloating. Dyspepsia is closely related to psychological factors such as stress because the gastrointestinal tract is very responsive to emotional stimuli and stress. Common stress among students is academic stress. This study aims to determine the effect of individual characteristics with dyspepsia symptoms and the emergence of dyspeptic symptoms due to academic stress during the COVID-19 pandemic. Methods: This study used a cross-sectional method to 192 University of Surabaya students taken from 8 faculties with consecutive sampling technique. The statistical test used is the sci-square test and the Spearman Rank correlation test. Results: There was a correlation between the level of academic stress and the incidence of functional dyspepsia in University of Surabaya students with the results of the Spearman Rank correlation test ((P value = 0.000) 0.10) and the correlation number of r = + 0.464 indicating a moderate correlation. Conclusion: There was an influence of individual characteristics (age, gender, faculty, and semester) with dyspepsia symptoms and the emergence of dyspepsia symptoms due to academic stress during the COVID-19 pandemic in students in Surabaya. Keywords: Dyspepsia, students, academic stress